Mechanics and Model-Based Control of Advanced Engineering Systems - Belyaev, Alexander K.; Irschik, Hans.; Krommer, Michael; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2014)
Mechanics and Model-Based Control of Advanced Engineering Systems collects 32 contributions presented at the International Workshop on Advanced Dynamics and Model Based Control of Structures and Machines, which took place in St. Petersburg, Russia in July 2012. The workshop continued a series of international workshops, which started with a Japan-Austria Joint Workshop on Mechanics and Model Based Control of Smart Materials and Structures and a Russia-Austria Joint Workshop on Advanced Dynamics and Model Based Control of Structures and Machines. In the present volume, 10 full-length papers based on presentations from Russia, 9 from Austria, 8 from Japan, 3 from Italy, one from Germany and one from Taiwan are included, which represent the state of the art in the field of mechanics and model based control, with particular emphasis on the application of advanced structures and machines.
Wave propagation in functionally graded material bar due to collision -- Rough dynamic response prediction for simple railway bridge subjected to high-speed trains -- Speed-gradient control of mechanical systems with constraints -- About coupling of the block elements -- Fractional derivative appearing in some dynamic problems -- Hydroelastic stability of single and coaxial cylindrical shells interacting with axial and rotational fluid flows -- Flexible robots: modeling and simulation -- Structural monitoring through acquisition of images -- SMA passive elements for damping in the stayed cables of bridge -- Temperature effects on the response of the bridge "OEBB Bruecke Grosshaslau" -- Controlled passage through resonance for two-rotor vibration unit -- High-strength network structure of jungle-gym type polyimide gels studies with scanning microscopic light scattering -- Extension of the body force analogy to generalized thermoelasticity -- Active vibration and noise control of a car engine: modeling and experimental validation -- Magnetic techniques for estimating elastic and plastic strains in steels under cyclic loading -- Induction machine torque control with self-tuning capabilities -- On equivalences in the dynamic analysis of layered structures -- Turbulent flow characteristics controlled by polymers -- Dynamic mechanical properties of functionally graded syntactic epoxy foam -- Problems of describing phase transitions in solids -- A non-linear theory for piezoelectric beams -- Nonlinear analysis of phase-locked loop -- Constitutive models for anisotropic materials susceptible to loading conditions -- Applicability of various fracture mechanics approaches for short fiber reinforced injection molded polymer composites and components -- The deformation-diffusion coupling in thin elastomeric gels -- Elastoplastic analogy constitutive model for rate-dependent frictional sliding -- Improved position control of a mechanical system using terminal attractors -- Convex design for lateral control of a blended wing body aircraft -- Observability and reachability, a geometric point of view -- The model of a deformable string with discontinuities at spatial description in the dynamics of a belt drive -- Doppler effects for dispersive waves in beam and plate with a moving edge -- Effect of road surface roughness on extraction of bridge frequencies by moving vehicle.
Keywords: Engineering; Mechanical engineering; Vibration; Engineering; Vibration, Dynamical Systems, Control; Mechatronics; Structural Mechanics